2020
DOI: 10.1016/j.atherosclerosis.2020.04.025
|View full text |Cite
|
Sign up to set email alerts
|

Surmounting the endothelial barrier for delivery of drugs and imaging tracers

Abstract: The endothelium serves as a refined barrier, crucial in guarding vascular homeostasis.• Impaired endothelial barrier function offers opportunities for targeted delivery of therapeutic agents/imaging tracers.• Nanosized technology provides the ability to distinguish between stable and rupture-prone atherosclerotic plaques.• The 'Trojan Horse Strategy' fools the endothelium and immune system in order to specifically deliver drugs at target sites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 79 publications
0
3
0
Order By: Relevance
“…Considering activated endothelium in atheromatous plaque, available active targets may be centered on expressed adhesion molecules, receptors as well as impaired function, such as P selectins, ICAM 1, VCAM 1, αVβ3 integrin, and LOX-1 major receptors for LDL uptake by ECs, 14 biosynthesis of NO, MCP-1 secretion. Overexpressed P and E selectins, ICAM 1, VCAM 1 induced by inflammatory stimuli, mediating leukocytes adhering to lesional region, are the hallmark of atherosclerosis.…”
Section: Focusing On Several Pivotal Cellsmentioning
confidence: 99%
“…Considering activated endothelium in atheromatous plaque, available active targets may be centered on expressed adhesion molecules, receptors as well as impaired function, such as P selectins, ICAM 1, VCAM 1, αVβ3 integrin, and LOX-1 major receptors for LDL uptake by ECs, 14 biosynthesis of NO, MCP-1 secretion. Overexpressed P and E selectins, ICAM 1, VCAM 1 induced by inflammatory stimuli, mediating leukocytes adhering to lesional region, are the hallmark of atherosclerosis.…”
Section: Focusing On Several Pivotal Cellsmentioning
confidence: 99%
“…In addition to direct exploitation of reconstituted HDL for treatment of disease, HDL-like nanoparticles are also explored for its utility to deliver drugs for treatment and tracers for imaging into the arterial wall or the brain or other tissues including cancers. The concept and state of the art of this strategy towards management of atherosclerosis is described extensively in another article of this review series [200]. Kratzer and colleagues demonstrated that proticle, nanoparticles made of protamines and oligonucleotides coated with apoA-I improve particle uptake and transcytosis through porcine brain capillary EC in vitro and that blocking SR-BI reduces transport to the level of uncoated proticles [201].…”
Section: Potential Relevance Of Transendothelial Hdl Transportmentioning
confidence: 99%
“…Targeted-imaging nanoparticles may also be used to specifically obtain information on the detail development and treatment of the specific lesions [11]. Recently, Schnitzler et al, [12] reported that the use of nanomedicines in drug delivery and tracer imaging improves the sensitivity and effectiveness of these agents intended for atherosclerotic diseases prevention by means of targeting the resident macrophages and activating the endothelial cells. Nanomedicines-based treatment has become an essential strategy for delivering safe and targeted nanoparticles to further reduce the residual risk of cardiovascular events [13].…”
Section: Introductionmentioning
confidence: 99%